Spontaneous rupture of the abdominal aorta. - Williams, T. G. (BMJ Group, 1977)
Fatal spontaneous rupture of the lower abdominal aorta in a previously healthy 61-year-old woman is reported; the possibility that she had the Ehlers-Danlos syndrome is discussed.